Biosensors Based on the Binding Events of Nitrilotriacetic Acid–Metal Complexes - Lin Zhu; Yong Chang; Yingying Li; Mingyi Qiao; Lin Liu (Biosensors, 2023)
Molecular immobilization and recognition are two key events for the development of biosensors. The general ways for the immobilization and recognition of biomolecules include covalent coupling reactions and non-covalent interactions of antigen–antibody, aptamer–target, glycan–lectin, avidin–biotin and boronic acid–diol. Tetradentate nitrilotriacetic acid (NTA) is one of the most common commercial ligands for chelating metal ions. The NTA–metal complexes show high and specific affinity toward hexahistidine tags. Such metal complexes have been widely utilized in protein separation and immobilization for diagnostic applications since most of commercialized proteins have been integrated with hexahistidine tags by synthetic or recombinant techniques. This review focused on the development of biosensors with NTA–metal complexes as the binding units, mainly including surface plasmon resonance, electrochemistry, fluorescence, colorimetry, surface-enhanced Raman scattering spectroscopy, chemiluminescence and so on.